2008
DOI: 10.1590/s0100-204x2008000100018
|View full text |Cite
|
Sign up to set email alerts
|

Hematological, biochemical and ruminant parameters for diagnosis of left displacement of the abomasum in dairy cows from Southern Brazil

Abstract: -The objective of this work was to evaluate hematological, biochemical and ruminant parameters for diagnosis and treatment of the left displaced abomasum (LDA) in dairy cows, in the Plateau Region of Rio Grande do Sul, Brazil. Ruminant fluid, blood and urine samples were collected from 20 cows suffering LDA and from 20 healthy cows (control). The cows with LDA showed lower values of daily milk production, body weight and corporal condition score. The use of pH reagent strips showed to be functional in the fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
14
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 19 publications
(16 reference statements)
17
14
0
4
Order By: Relevance
“…Glucose values reported in this study are in agreement with the ϐindings of other Brazilian researchers (González 2000, Campos et al 2007, Cardoso et al 2008, González et al 2009, Souza & Junior 2009). The lowest concentration of serum glucose was at calving.…”
Section: Discussionsupporting
confidence: 93%
“…Glucose values reported in this study are in agreement with the ϐindings of other Brazilian researchers (González 2000, Campos et al 2007, Cardoso et al 2008, González et al 2009, Souza & Junior 2009). The lowest concentration of serum glucose was at calving.…”
Section: Discussionsupporting
confidence: 93%
“…The highest values of this parameter (87.62 g·dm -3 ) were found at the end of the experiment, in cows fed with maize silage covered with oxo-biodegradable foil. As in own studies, other authors (Mordak and Nicpoń, 2006;De Cardoso et al, 2008;Adamski, 2010) observed exceeding of the reference range (Winnicka, 2015) for the evaluated parameter by 18, 23 and 19%, respectively. Adamski et al (2010) showed that the serum total protein level in cows at 8 weeks of lactation decreased as the condition of these animals increased from 84.52 g·dm -3 at BCS (Body Condition Score) 1-3 to 72.38 g·dm -3 of the fatted cows (BCS≥4).…”
Section: Resultssupporting
confidence: 72%
“…No Brasil, este padrão de casuística é mantido, existindo relatos no Estado de São Paulo, onde a relação de DAE e DAD é de 5:1 (Birgel et al 1990), enquanto no Paraná tal relação aumenta para 8 a 9:1 (Reichert Netto 1992). Existem ainda relatos de DA em bovinos leiteiros em Pernambuco (Coutinho et al 2002, Câmara et al 2007, Goiás (Silva et al 2004(Silva et al , 2008, Distrito Federal ) e Rio Grande do Sul (Cardoso et al 2008); enquanto em bovinos de corte, apenas no Distrito Federal (Câmara et al 2009). Assim como outras doenças da produção (metrite, retenção de placenta, cetose, hipocalcemia, mastite, doença cística ovariana), o DA acarreta grande perda econômica na indústria leiteria e diminui o bem-estar animal (Ingvartsen et al 2003, Mullingan & Doherty 2008.…”
Section: Introductionunclassified